The perils of Persiles and Sigismunda, a Northern saga by Miguel de Cervantes - Cervantes Saavedra, Miguel de 1547-1616 (Foundations (ARC Humanities Press), 2024)
Los trabajos de Persiles y Sigismunda, historia septentrional (1617) is Miguel de Cervante's last major work. Virtually ignored for the past four hundred years and overshadowed by the acclaim accorded Don Quixote, it is due a revival. As indicated by this new English title, The Perils of Persiles and Sigismunda, a Northern Saga, this challenging saga-like fiction follows an attractive young prince and princess who undertake a perilous pilgrimage by sea and on land from their North Atlantic islands to Rome. This new translation by William Thomas Little takes full account of recent scholars' ground-breaking research and their new readings. It also includes a selected bibliography, a contextualizing introduction, and footnotes on the text that clarify for contemporary readers cultural issues that were readily known to seventeenth-century readers in Spain, France, Italy, Portugal, and England